An Image Signal Accumulation Multi-Collection-Gate Image Sensor Operating at 25 Mfps with 32 × 32 Pixels and 1220 In-Pixel Frame Memory - Dao, Vu Truong Son (Sensors (Basel), 2018)
The paper presents an ultra-high-speed image sensor for motion pictures of reproducible events emitting very weak light. The sensor is backside-illuminated. Each pixel is equipped with the multiple collection gates (MCG) at the center of the front side. Each collection gate is connected to an in-pixel large memory unit, which can accumulate image signals captured by repetitive imaging. The combination of the backside illumination, image signal accumulation, and slow readout from the in-pixel signal storage after an image capturing operation offers a very high sensitivity. Pipeline signal transfer from the MCG to the in-pixel memory units enables the sensor to achieve a large frame count and a very high frame rate at the same time. A test sensor was fabricated with a pixel count of 32 × 32 pixels. Each pixel is equipped with four collection gates, each connected to a memory unit with 305 elements; thus, with a total frame count of 1220 (305 × 4) frames. The test camera achieved 25 Mfps, while the sensor was designed to operate at 50 Mfps.